2014
DOI: 10.1002/jms.3402
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of gas‐phase ion/molecule reaction of carbon dioxide with phenide ions

Abstract: On contrary to the widely accepted conviction that the m/z 93 ion derived from phenol does not react with CO2, we demonstrate that it makes an adduct with CO2 to a small but demonstrable extent. For example, the product-ion mass spectrum recorded for the m/z 98 ion derived from [(2)H6]phenol showed a small peak at m/z 142 when CO2 was used as the collision gas. The formation of an m/z 137 adduct ion from the m/z 93 ion (generated either directly from phenol, or indirectly from salicylic acid by in-source decar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…To start with, we pursued to find out whether the anilide ion would add to CO 2 in a manner similar to that reported for phenoxide and phenide ions [8,9]. Our preliminary results indicated that the anilide ion undergoes facile addition to CO 2 .…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…To start with, we pursued to find out whether the anilide ion would add to CO 2 in a manner similar to that reported for phenoxide and phenide ions [8,9]. Our preliminary results indicated that the anilide ion undergoes facile addition to CO 2 .…”
Section: Resultsmentioning
confidence: 92%
“…A ratio calculation after peak integration showed that the relative peak area of the m/z 137 peak was about 3.8 when normalized to that of the m/z 136 peak. Evidently, the anilide ion demonstrates a strong affinity to CO 2 compared with the extremely mediocre affinity shown by the phenoxide ion [9].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations